Avoidance of neonicotinoid-treated seeds and cotyledons by captive eared doves (Zenaida auriculata, Columbidae) - Addy Orduna, Laura (2022)
Farmland birds can be exposed to neonicotinoids through the ingestion of treated unburied seeds and cotyledons. The aim of this study was to evaluate the avoidance of sorghum with imidacloprid, clothianidin or thiamethoxam, soybean with imidacloprid, and soybean cotyledons with imidacloprid or thiamethoxam on eared doves (Zenaida auriculata). Doves were fed with test food (untreated and neonicotinoid-treated sorghum, soybean or soybean cotyledons) and maintenance food (seed mix) for 3–5 days to study the repellency (primary repellency and conditioned aversion) and anorexia caused by neonicotinoid-treated food, followed by a 7-day period on maintenance food to study the persistence of the anorexic effect after neonicotinoid exposure. Immediately afterward, the same doves were exposed to treated test food during a second period of 3–5 days to study the potential reinforcement of food avoidance. Finally, doves were fed with untreated test food to test the capacity of the pesticide to induce conditioned food aversion against untreated food in subsequent encounters. Intoxication signs and differences of body weight were determined. With sorghum, the three neonicotinoids produced a decrease in the consumption of treated seeds by >97% compared to control birds. However, this was not enough to prevent the death of 3/8 and 1/8 of the doves exposed to imidacloprid and clothianidin, respectively. Anorexia was clearly observed with neonicotinoid-treated sorghum. The birds did not avoid the untreated sorghum after exposure to the treated sorghum, indicating that avoidance is not generalized to the type of food without an associated sensory cue. The results obtained with soybean seeds and cotyledons were less conclusive because captive doves hardly consumed these foods, even without neonicotinoid treatment. The avoidance of sorghum seeds treated with neonicotinoids was insufficient to prevent poisoning and death of eared doves.